HUBUNGAN ANTARA MANUSIA, MASYARAKAT, DAN BUDAYA DALAM PERSPEKTIF ISLAM - Zulkarnain Dali (Universitas Islam Negeri Fatmawati Sukarno, 2016)
In life-paced world in the meantime, of course we are always in touch or need one samalainnya. It has become sunahtullah of the creator of the universe. Therefore, the following article will discuss the relationship between man, society and culture are viewed from the perspective of Islam. Certainly in this article does not discuss in detail the relationship between the three items above in the view of Islam, but only discussed in general terms